Tip-induced deformation of a phospholipid bilayer: Theoretical perspective of sum frequency generation imaging - Volkov, Victor (The Journal of chemical physics, 2014)
The paper addresses theory of Sum Frequency Generation imaging of an atomic force microscopy tip-induced deformation of a bilayer phospholipid membrane deposited over a pore: known as a nano-drum system. Image modeling employed nonlinearities of the normal modes specific to hydrocarbon terminal methyls, which are distributed about the deformed surfaces of inner and outer leaflets. The deformed profiles are according to the solutions of shape equation for Canham-Helfrich Hamiltonian accounting properties of four membranes, which differ in elasticity and adhesion. The results indicate that in continuous deformed surfaces, the difference in the curvature of the outer and inner leaflets dominates in the imaged nonlinearity. This is different comparing to the results for a perfect bilayer spherical cap system (the subject of previous study), where nonlinear image response is dominated by the mismatch of the inner and outer leaflets’ surface areas (as projected to the image plane) at the edge of perfectly spherical structure. The results of theoretical studies, here, demonstrate that Sum Frequency Generation imaging in continuous and deformed bilayer surfaces are helpful to address curvature locally and anticipate mechanical properties of membrane. The articles discuss applicability and practical limitations of the approach. Combination of Atomic Force Microscopy and Sum Frequency Generation imaging under controlled tip-induced deformation provides a good opportunity to probe and test membranes physical properties with rigor of adopted theory.